Whose Energy Future? Indonesia’s Paradox Of Coal-Dependent Transition - Sutrisno, Alya Triska (Universitas Riau Kepulauan, 2026)
Indonesia’s energy transition presents a paradox: while the state commits to decarbonization, coal remains central to national energy and industrial policy. This study examines the challenges facing energy democracy in Indonesia amidst the ongoing energy transition within the coal sector. This article investigates how state-led energy transitions policies under the Joko Widodo administration reconfigure coal as part of a “green” development pathway and the implications for energy democracy. The study employs a qualitative methods by review analysis of policy documents, academic literature, and civil society reports to examine policy framing, governance arrangements, and community impacts. Drawing on political ecology, green grabbing, and energy democracy frameworks, the analysis shows that centralized decision-making enables coal infrastructure to persist through mechanism such as biomass co-firing, downstream industrialization, and strategic industry exemptions. The article contributes to energy transition scholarship by showing how decarbonization policies can simultaneously advance climate commitments and reproduce extractive governance. Rather than a shift away from fossil fuels, Indonesia’s transition represents a reconfiguration of coal dependence within a green developmental framework, raising question about the feasibility of energy democracy in centralized energy systems.